Enzymatic and structural analysis of the I47A mutation contributing to the reduced susceptibility to HIV protease inhibitor lopinavir - Grantz Šašková, Klára; Kožíšek, Milan; Lepšík, Martin; Brynda, Jiří; Řezáčová, Pavlína; Václavíková, Jana; Kagan, Ron M; Machala, Ladislav; Konvalinka, Jan (Protein science, 2008)
Lopinavir (LPV) is a second-generation HIV protease inhibitor (PI) designed to overcome resistance development in patients undergoing long-term antiviral therapy. The mutation of isoleucine at position 47 of the HIV protease (PR) to alanine is associated with a high level of resistance to LPV. In this study, we show that recombinant PR containing a single I47A substitution has the inhibition constant (K(i) ) value for lopinavir by two orders of magnitude higher than for the wild-type PR. The addition of the I47A substitution to the background of a multiply mutated PR species from an AIDS patient showed a three-order-of-magnitude increase in K(i) in vitro relative to the patient PR without the I47A mutation. The crystal structure of I47A PR in complex with LPV showed the loss of van der Waals interactions in the S2/S2' subsites. This is caused by the loss of three side-chain methyl groups due to the I47A substitution and by structural changes in the A47 main chain that lead to structural changes in the flap antiparallel beta-strand. Furthermore, we analyzed possible interaction of the I47A mutation with secondary mutations V32I and I54V. We show that both mutations in combination with I47A synergistically increase the relative resistance to LPV in vitro. The crystal structure of the I47A/I54V PR double mutant in complex with LPV shows that the I54V mutation leads to a compaction of the flap, and molecular modeling suggests that the introduction of the I54V mutation indirectly affects the strain of the bound inhibitor in the PR binding cleft.
Keywords: kinetika; financování organizované; Catalysis; vodíková vazba; Kinetics; Hydrogen-Ion Concentration; Escherichia coli; katalýza; substituce aminokyselin; inhibitory HIV-proteasy; lidé; rekombinantní proteiny; Recombinant Proteins; pyrimidinony; Amino Acid Substitution; HIV Protease Inhibitors; Models, Molecular; Financing, Organized; virová léková rezistence; Computational Biology; Protein Structure, Secondary; molekulární modely; HIV Protease; Disease Susceptibility; sekundární struktura proteinů; Hydrogen Bonding; Drug Resistance, Viral; HIV-proteasa; Pyrimidinones; alanin; výpočetní biologie; koncentrace vodíkových iontů; Alanine; náchylnost k nemoci; Humans